Birth Defects: A Hospital Based Study in Chittagong, Bangladesh (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Introduction: Birth defects are one of the most common causes of disability in developed and developing countries. Birth defects are structural or functional anomalies, including metabolic disorders, which are present at the time of birth. Although the worldwide incidence of birth defects is estimated at 3-7%, the rate varies widely between countries. In this paper, we categorized the birth defects most commonly seen in Bangladesh and their outcome. We hope to use this information to guide the strategies used to manage these problems.Materials and Methods: This hospital based, descriptive study was done in the Department of Pediatric Surgery in Chittagong Medical College and Hospital from January 2008 to December 2012. Records of all patients with birth defects in our hospital and departmental database were reviewed. Types of birth defects, age, sex, surgery performed and outcome were analyzed in patients admitted during this period. Data were analyzed by SPSS 17. Statistical analysis was performed by the chi-square test and mean and percentage values were calculated. P